Alignment of 17O-enriched water–endofullerene H2O@C60 in a liquid crystal matrix. (21st September 2018) - Kouřil, Karel; Meier, Benno; Alom, Shamim; Whitby, Richard J.; Levitt, Malcolm H.
Abstract : The water molecule in H2 O@C60 endofullerene, dissolved in a nematic liquid crystal, is aligned with its plane perpendicular to the liquid crystal director. Abstract : We present a 17 O and 1 H NMR study of molecular endofullerene H2 O@C60 dissolved in the nematic liquid crystal N -(4-methoxybenzylidene)-4-butylaniline (MBBA). The 17 O NMR peak is split into five components by the 17 O residual quadrupolar coupling, each of which is split into a triplet by the 1 H– 17 O residual dipolar coupling and scalar coupling. The splittings are analysed in terms of the partial alignment of the encapsulated water molecules. Order parameters describing the alignment are estimated. It is found that the preferential orientation of the endohedral water molecule has the molecular plane perpendicular to the liquid crystal director.